Determination of Cytokine Levels in Joint Fluid as an Alternative Option for Examination of Internal Temporomandibular Joint Disorders - P. Tvrdý; P. Heinz; L. Hrdina; A. Galandáková; J. Pazdera (Czech Dental Chamber, 2011)
Cytokines are extracellular peptides that mediate the strong stimulatory or inhibitory effects on most biological cells. Originally they were considered as candidates for supporting processes of the immune response. It is now clear that they are involved in most physiological processes. They also act as mediators of infectious, inflammatory and immune diseases, including procurement related degenerative changes in tissues. Elevated level of interleukins IL-6, IL-1beta and IL-8 is directly linked to the pathogenesis of inflammatory and degenerative joint changes.The authors presents a 10 patients pilot study of the use of determining the levels of selected interleukins IL-6 and IL-8 in the diagnosis of temporomandibular joint disorders. This examination can be supplemented with an algorithm established by clinical and imaging diagnostic methods and also to assess the efficacy of treatment.